2022
DOI: 10.1111/jace.18656
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the injected electron concentration and thermionic emission property in C12A7:e ceramic via Al site Zr doping

Abstract: Ca 24 Al 28 O 64 ] 4+ (4e − ) (C12A7:e − ) has excellent potential in electric propulsion owing to various advantages, including low work function, low working temperature, and stable chemical properties. However, increasing electron concentration enhances the thermionic emission property of C12A7:e − . This study used a chemical method-spark plasma sintering to synthesize Zr-doped C12A7:e − (C12(A 1 − x Z x )7:e − , where x = 0 to 0.14). The study results show that C12(Al 0.86 Zr 0.14 )7:e − maximum injected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
27
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(30 citation statements)
references
References 38 publications
3
27
0
Order By: Relevance
“…3 This preliminarily indicated that the [Ca 24 Al 24.08 Zr 3.92 O 64 ] 4+ (4e − ) sample with good compactness was successfully synthesized in one step by SPS sintering. 3,5 In addition, the color of the synthesized block is metallic black, which is caused by the transition of electrons in the block. This preliminarily indicates that the injection of high-density free electrons is achieved in the synthetic block.…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…3 This preliminarily indicated that the [Ca 24 Al 24.08 Zr 3.92 O 64 ] 4+ (4e − ) sample with good compactness was successfully synthesized in one step by SPS sintering. 3,5 In addition, the color of the synthesized block is metallic black, which is caused by the transition of electrons in the block. This preliminarily indicates that the injection of high-density free electrons is achieved in the synthetic block.…”
Section: Resultsmentioning
confidence: 93%
“…[Ca 24 Al 24.08 Zr 3.92 O 64 ] 4+ (4e − ) electrides are a low work functions(∼2.4 eV) material that can store high-density (∼10 21 cm −3 ) free electrons. [1][2][3][4][5][6][7][8][9][10] Its crystal structure is composed of high-density (∼10 21 cm −3 ) subnanometer cage cavities and there are electron transmission channels between cage cavities (as shown in Figure 1). [2][3][4][5][6][7][8] This cage structure with electronic storage enables [Ca 24 Al 24.08 Zr 3.92 O 64 ] 4+ (4e − ) to have good physical and chemical stability, low work function (∼2.4 eV), [16][17][18][19][20][21][22][23][24][25][26][27][28] and outstanding electron emission potential.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such a consistent description of the transport properties is necessary to evaluate current doping strategies. 26,27 For example, the isovalent substitution of Ca 2+ by Sr 2+ or Bi 2+ is proposed in order to widen the cages and facilitate hopping transport between the cages. 28,29 Another alternative is substituting Al 3+ by Zr 4+ in the cage framework in order to further increase the electron density.…”
Section: Introductionmentioning
confidence: 99%
“…28,29 Another alternative is substituting Al 3+ by Zr 4+ in the cage framework in order to further increase the electron density. 27 Predictions of the impact of doping on the electronic structures of C12A7 and C12A7 : 2e À and their actual electronic transport properties by ab-initio approaches are extremely difficult. Supplementing ab initio calculations of the electronic structure of doped mayenite or doped mayenite-electride by a comparison of experimental data with empirical transport models, which correlate transport mechanisms with electronic structures (e.g., with the energy levels and the effective densities of states), helps bridging the gap between experimental observations and ab initio predictions.…”
Section: Introductionmentioning
confidence: 99%